INTEGRATION OF SPEECH DEVELOPMENT AND PHYSICAL EDUCATION THROUGH INTEGRATED EXERCISES AND GAMES - Spasic, Jelena Lj.; Stanković, Slađana; Jančić, Jelena (Metodička teorija i praksa, 2026)
The paper presents possibilities for integrating speech development and physical education in working with preschool children. An integrative approach is one of the most important elements of the modernization of educational practice, which is also emphasized in the Osnove programa predškolskog vaspitanja i obrazovanja – Godine uzleta. The paper provides examples of integrated activities that are based on a logical and purposeful connection of content in the areas of speech development and physical education. The contribution of the work is reflected in concrete examples tested in practice, within the framework of integrated planned learning situations that are implemented within the framework of methodological practicums by students of the Preschool Teacher program at the Faculty of Education in Jagodina.
Keywords: methodology of speech development; methodology of physical education; integration; integrative approach; preeschool age